A novel metastable state magnetic phase of monolayer FeSe. (21st March 2018) - Meng, Lijun; Yu, Jun; Peng, Haiyan; Li, Yanru; Zhong, Jian-Xin
Abstract: We found a novel metastable magnetic phase by systematically calculating total energy of monolayer FeSe in various antiferromagnetic (AFM) orders using first-principles method. The new metastable magnetic phase named as QAFM is a magnetic state with short-range magnetic structure which can be regarded as a transitional state between checkerboard-like AFM state and collinear AFM state. Both magnetic moments with important fluctuation and charge density difference with a 2 × 4 reconstruction of orbitals breaks C 4 symmetry and possibly commonly corresponds to the nematic phase in recent transmission electron microscopy and neutron scattering experiment observations. Its electronic band displays a Dirac-like band structure along Γ– X in the folding Brillouin zone of the supercell. The QAFM phase of FeSe holds metallic feature with d xz, d yz and d z 2 band crossing Fermi level even including spin–orbit coupling. Additionally, the weight of 3 d orbitals varies as the applied expansion strain which may be directly correlated with the emerging nematic phase and superconducting state of strained monolayer FeSe. The finding of novel magnetic order may provide important clues to elucidate the relationship of antiferromagnetism and superconductivity for unconventional Fe-based superconductor.